Detection of Alcohol in Alleged Users:A 5 Year Study - Romana Malik ,Babur Rashid Chughtai,Riffet Khursheed,Misbah Amanat (Journal of Rawalpindi Medical College, 2016)
Background: To access the frequency of drinking reported cases and positive cases of alleged drinking. Methods: In this Observational study all persons who presented with suspicion of alcohol intake, in the department of Chemical Examiner Govt of Punjab, Rawalpindi, were included. During five years, total specimens from 2655 persons were received for detection of alcohol. Total data was scrutinized with reference to year wise cases, total number of cases, number of positive/negative cases and age wise analysis. Results: During the tenure of 5 years, samples of total 2655 persons of alleged alcohol intake were received for detection of alcohol. Alcohol was detected in majority (98.31%) of the cases. Most common age group was 30-40 years (40.19%). 2nd most consumer age group was 40-50 years with total 661 (24.9%) persons involved. Only 398 (14.99%) persons of age above 50 years were referred for detection of alcohol. Conclusion: There is dire need to introduce breathalyzer test in our country to reduce the number of drinking related accidents. There is also need to use most modern techniques and apparatus to know the BAC (blood alcohol concentration)